THE IMPLEMENTATION OF CREATING SHARED VALUE (CSV) AS A REFERENCE FOR CSR DEVELOPMENT BASED ON SOCIAL ENTREPRENEURSHIP (CASE STUDY AT PT NESTLE INDONESIA) - Dwiputra, SE, Nuruddin Ahmad (Jurnal Ilmiah Mahasiswa FEB, 2013)
Nestle is multinational company which is very concerned with the quality and usefulness of the product with the creation. One of the main Nestle CSV programs is the Rural Development that aim to improve the quality of life Dairy Farmers. This study aims to understand the implementation of the NestlÃ© CSV program in rural development sector as a reference to formulate an alternative CSR activities based on social entrepreneurship. This study use a qualitative descriptive method that using two case studies on the Nestle partner namely Jabung Agro Niaga Cooperative and Pujon SAE Cooperative. The data used for this study using primary and secondary data, such as the results of the interviews conducted with the managers of both cooperatives and corporate reports and other publication. This study concluded that Nestle has actually implement the rural Development program to improve the quality of life of dairy farmers. And the success of the Nestle CSV can be used as guidelines for creating another CSR program based on Social Entrepreneurship. Keywords : CSR. Creating Shared Value, Community Development, Social Entrepreneurship